Developing Country Debt and Economic Performance, 3 : Country Studies--Indonesia, Korea, Philippines, Turkey. - Sachs, Jeffrey (National Bureau of Economic Research project report., 1990)
For dozens of developing countries, the financial upheavals of the 1980s have set back economic development by a decade or more. Poverty in those countries has intensified as they struggle under the burden of an enormous external debt. In 1988, more than six years after the onset of the crisis, almost all the debtor countries were still unable to borrow in the international capital markets on normal terms. Moreover, the world financial system has been disrupted by the prospect of widespread defaults on those debts. Because of the urgency of the present crisis, and because similar crises have r.